1983
DOI: 10.1152/jappl.1983.54.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperoxia on metabolic and catecholamine responses to prolonged exercise

Abstract: The use of inspired gas mixtures with an oxygen fraction in excess of 0.3 has been associated with a decrease in the gas exchange ratio (R) during prolonged work in humans. It had been hypothesized that the lower R was due to a lower plasma catecholamine concentration caused by the hyperoxia (Med. Sci. Sports 10: 167-170, 1978). We tested this hypothesis by measuring changes in plasma epinephrine and norepinephrine when the subjects were switched from breathing air to 60% O2 (and vice versa) during 40 min of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The slight but significant increase in V O 2 ( (14,20,23,32) and to increase locomotor muscle V O 2 (28).…”
Section: Characteristics and Causes Of Muscle Fatiguementioning
confidence: 94%
“…The slight but significant increase in V O 2 ( (14,20,23,32) and to increase locomotor muscle V O 2 (28).…”
Section: Characteristics and Causes Of Muscle Fatiguementioning
confidence: 94%
“…Some authors have reported no significant difference in _ V V O 2 during submaximal exercise (Adams and Welch 1980;Byrnes et al 1984;Welch and Pedersen 1981), while three studies found an increase in _ V V O 2 under hyperoxia (Graham and Wilson 1983;Hogan and Welch 1984;Howley et al 1983). In spite of these contradictory results, it has been suggested that the body's metabolic response changes during exercise under hyperoxia (Howley et al 1983;Welch and Pedersen 1981).…”
Section: Introductionmentioning
confidence: 99%
“…As we conducted this operation in the two ambiances, there should be no methodological bias relative to this technique in one condition compared to the other. Besides, several studies with different measurement techniques such as Douglas bags (Wilson et al 1975), automatic systems (Prieur et al 2002), mixing chamber (Howley et al 1983) or different analysers such as micro-Scholander apparatus (Wilson et al 1975;Howley et al 1983), mass spectrometer (Peltonen et al 2001b), electrochemical (Prieur et al 2002) or paramagnetic analyzers (present study) evidenced a rise of _ V O 2 in hyperoxia. On the other hand, it has been shown (Hornby et al 1995) that infrared analyser underestimates F E CO 2 when not using hyperoxic calibration gases (e.g.…”
Section: Discussionmentioning
confidence: 50%
“…The only greater oxidation of fatty acids during hyperoxia proposed by several authors appears here to be insufficient to explain the whole _ V O 2 excess. Moreover, studies from Howley et al (1983), Adams et al (1986) and Linossier et al (2000) concluded that blood levels of free fatty acids were similar and that there was no glycogen sparing during exercise in hyperoxia. Thus, there should be another mechanism responsible for the O 2 overconsumption in hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation